The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11356-014-3191-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of in vitro high-density polyethylene (HDPE) degradation by physical, chemical, and biological treatments

Abstract: Partially degraded high-density polyethylene (HDPE) was collected from plastic waste dump yard for biodegradation using fungi. Of various fungi screened, strain MF12 was found efficient in degrading HDPE by weight loss and Fourier transform infrared (FT-IR) spectrophotometric analysis. Strain MF12 was selected as efficient HDPE degraders for further studies, and their growth medium composition was optimized. Among those different media used, basal minimal medium (BMM) was suitable for the HDPE degradation by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…It has been shown that oxidation of PE enhanced hydrophilicity and ultimately facilitated PE biodegradation [34,35,36]. Some pretreatments, including photo-oxidation, thermal treatment, and acid treatment, have been shown to accelerate the oxidation and degradation of PE [37].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that oxidation of PE enhanced hydrophilicity and ultimately facilitated PE biodegradation [34,35,36]. Some pretreatments, including photo-oxidation, thermal treatment, and acid treatment, have been shown to accelerate the oxidation and degradation of PE [37].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the previously reported work in Aspergillus spp. like Aspergillus terreus (Balasubramanian et al, 2014), A. niger (Volke et al, 2001), Aspergillus cremeus, Aspergillus ornatus, Aspergillus glaucus, Aspergillus candidus, Aspergillus nidulans, A. flavus and Aspergillus oryzae (Konduri et al, 2010) suggested the pretreatment of HDPE. Hence, the potential HDPE degraders, A. tubingensis VRKPT1 and A. flavus VRKPT2 has shown up highest degradation rate without any pre-treatment and pro-oxidant additive (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Biodegradation of polymers primarily focuses on increasing the surface hydrophobicity, thereby enhancing microbial attachment. Hence, most of the researchers recommend pretreatment (Arkatkar et al, 2010;Balasubramanian et al, 2014) for efficient microbial adherence. Such treatments result in the formation of carbonyl, carboxyl and ester functional groups that decreases the hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently the polymeric backbones are cleaved by different hydrolytic enzymes (as well as other catalytic agents such as free radicals) produced by the biodegrading microorganisms. This results in the progressive reduction of the molecular weight of the polymer [32]. Some of the degradation products can be assimilated by the micro-organisms leading to mineralization of organic compounds and generation of new biomass.…”
Section: Weight Reductionmentioning
confidence: 99%
“… Kocuria palustris M16 LDPE (20µm) 30 days 1±0.033 [ 32 ] 14. Bacillus pumilus M27 LDPE (20µm) 30 days 1.5 ± 0.038 [ 32 ] 15. Bacillus subtilis H1584 LDPE (20µm) 30 days 1.75 ± .06 [ 32 ] 16.…”
Section: Introductionmentioning
confidence: 99%